Biological Drivers of Wilms Tumor Prognosis and Treatment - Hannah M. Phelps; Saara Kaviany; Scott C. Borinstein; Harold N. Lovvorn (MDPI AG, 2018)
Prior to the 1950s, survival from Wilms tumor (WT) was less than 10%. Today, a child diagnosed with WT has a greater than 90% chance of survival. These gains in survival rates from WT are attributed largely to improvements in multimodal therapy: Enhanced surgical techniques leading to decreased operative mortality, optimization of more effective chemotherapy regimens (specifically, dactinomycin and vincristine), and inclusion of radiation therapy in treatment protocols. More recent improvements in survival, however, can be attributed to a growing understanding of the molecular landscape of Wilms tumor. Particularly, identification of biologic markers portending poor prognosis has facilitated risk stratification to tailor therapy that achieves the best possible outcome with the least possible toxicity. The aim of this review is to (1) outline the specific biologic markers that have been associated with prognosis in WT and (2) provide an overview of the current use of biologic and other factors to stratify risk and assign treatment accordingly.